Electronic Church, media religiosity, mediatized religiosity: concepts to reflect on the relationship between media and religion - Sousa, Marco Túlio de (MATRIZes, 2021)
The increasing number of studies on media and religion has favored the emergence of different views on the phenomenon, resulting in different methodologies, theories, and concepts. This paper discusses the recurrent concepts used by researchers in this area, especially in Brazil, showing how they help us understand particular aspects of this problem, as well as its possible limitations. Through a bibliographic review, we reflect on the productivity of general concepts like “the electronic church,” “media religiosity,” “mediatized religiosity” to think on the transformations of contemporary religion in its interconnections with the media.